Exploring the Relationships Between Perceived Leadership Style, Job Satisfaction, and Academic Service Quality Among Cambodian Public University Staff - Menh, Sophea; Kouy, Sokean; Pok, Visalbot; Mok, Sarom; Em, Sereyrath (Journal of Basic Education Research, 2025)
Purpose of the Study: This study aims to investigate the current self-perceptions of public university staff in Cambodia regarding transformational leadership components, job satisfaction, and academic service quality. Methodology: This study employs the quantitative research design. A sample of 336 staff from three selected public universities located in Phnom Penh completed the Multifactor Leadership Questionnaire (MLQ) to measure transformational leadership (TRL) dimensions, the Minnesota Satisfaction Questionnaire (MSQ) to measure the level of job satisfaction (JOS), the Service Quality (SERVPERF) to measure academic service quality (ASQ), and a demographic survey. The collected data were analyzed using descriptive and inferential statistics. Main Findings: The study found that public university staff in Cambodia perceived TRL, JOS, and ASQ were at high levels. Ranking from the highest to the lowest mean scores were TRL, JOS, and ASQ, respectively. It was also revealed that there were favorable correlations between TRL dimensions, JOS, and ASQ. This indicates that the TRL dimensions exhibited stronger positive relationships. Every correlation was statistically significant at the 0.01 level. Novelty/Originality of this Study: Through this study, the significance of transformative leadership behavior and its connection to job satisfaction and academic service quality were better understood. The findings of this study offer empirical research on this subject in higher education, which advances the field of leadership studies